Advances in engineering materials, product and systems design : special topic volume with invited peer reviewed papers only - Subic, Aleksandar (Advanced materials research, 2013)
This book presents some recent research efforts that provide new insights into particular advances in engineering materials, product and systems design. The featured research contributions stemming from an international virtual engineering forum aim to inform future research and development in relevant fields. This includes especially research focused on design, materials and manufacturing of engineering structures, components and systems for industrial applications, including aerospace, automotive, bioengineering and sports. Review from Book News Inc.: The 15 papers in this collection, submit.